Market leadership in the Brazilian automotive industry: The case of Marcopolo - Luiz Ricardo Mattos Teixeira Cavalcante; Bruno César Pino Oliveira de Araújo (Institute for Applied Economic Research (ipea), 2015)
The aim of this paper is to analyze the factors that explain the industrial leadership of a Brazilian bus bodywork manufacturer (Marcopolo). From a methodological point of view, the paper was a case study based on bibliographic review and on in-depth interviews. The underlying hypothesis is that, at some point in the past, some idiosyncratic factors regarding Brazilian market led the large auto manufacturers to give up contesting Brazilian incumbents in these segments. Then, Brazilian companies managed to grow hand-in-hand with the Brazilian automotive market, and dictated the customer-supplier relationship patterns. Marcopolo had to develop technological and organizational capabilities related to stock management, and lean production principles of modularity and product platforms or families, very important to its CKD exports. Recently, Marcopolo found its own way to internationalization, especially towards developing countries (Marcopolo is present in all BRIC countries), through acquisition of existing plants, joint-ventures and involvement of local suppliers. In sum, Marcopolo's strategies and decisions - going public, exporting and FDI - have been ahead of the Brazilian public policy discourse or market trends. These strategies were clearly riskier, but once succeeded, help to understand Marcopolo's leading position.
Keywords: L62; 330; Marcopolo; automobile industry; market leadership; bus bodywork manufacturing